PPAT as the Reporting Party for Suspicious Financial Transactions Post Government Regulation Number 43 of 2015 - Anggraini, Tasya; Madjid, Abdul; Widhiawati, Dyah (International Journal of Business, Law, and Education, 2024)
This study is motivated by PPAT's obligations as the reporting party for suspicious financial transactions which conflict with the code of ethics of the PPAT profession and also result in regulatory inconsistencies so that it gives multiple interpretations for each PPAT individual. The aims of this study are to (1) review PPAT's obligations from Government Regulations and code of ethics, (2) determine the legal consequences if PPAT does not report suspicious transactions. This study used a normative juridical legal research type and used a statutory approach and a conceptual approach. The result of this study is that the code of ethics is not included in statutory regulations so that the provisions in Government Regulations can ignore the code of ethics.